Time spent on self‐management by people with diabetes: results from the population‐based KORA survey in Germany. Issue 8 (7th November 2018) - Icks, A.; Haastert, B.; Arend, W.; Konein, J.; Thorand, B.; Holle, R.; Laxy, M.; Schunk, M.; Neumann, A.; Wasem, J.; Chernyak, N.
Abstract: Aims: Time needed for health‐related activities in people with diabetes is assumed to be substantial, yet available data are limited. Time spent on self‐management and associated factors was analysed using cross‐sectional data from people with diagnosed diabetes enrolled in a population‐based study. Methods: Mean total time spent on self‐management activities was estimated using a questionnaire for all participants with diagnosed diabetes in the KORA FF4 study ( n = 227, 57% men, mean age 69.7, sd 9.9 years). Multiple two‐part regression models were fitted to evaluate associated factors. Multiple imputation was performed to adjust for bias due to missing values. Results: Some 86% of participants reported spending time on self‐management activities during the past week. Over the entire sample, a mean of 149 (sd 241) min/week were spent on self‐management‐activities. People with insulin or oral anti‐hyperglycaemic drug treatment, better diabetes education, HbA1c 48 to < 58 mmol/mol (6.5% to < 7.5%) or lower quality of life, spent more time on self‐management activities. For example, people without anti‐hyperglycaemic medication invested 66 min/week in self‐management, whereas those taking insulin and oral anti‐hyperglycaemic drugs invested 269 min/week (adjusted ratio 4.34, 95% confidence interval 1.85–10.18). Conclusions: Time spent on self‐management activities by people with diabetes was substantial and varied with an individual's characteristics. Because of the small sample size and missing values, the results should be interpreted in an explorative manner. Nevertheless, time needed for self‐management activities should be routinely considered because it may affect diabetes self‐care and quality of life. What's new?: Few studies have analysed time spent on self‐management activities in diabetes. Factors associated with patterns of health‐related activities remain under‐researched. This population‐based study analysed a comprehensive set of self‐management activities in people with diabetes. In our entire sample, an average of 2.5 h/week were spent on self‐management activities. Time investments differed according to diabetes treatment, diabetes education, HbA1c and quality of life. Time needed for self‐management activities should be routinely considered because it may affect diabetes self‐care and quality of life.